2011
DOI: 10.1002/prot.23225
|View full text |Cite
|
Sign up to set email alerts
|

Longer simulations sample larger subspaces of conformations while maintaining robust mechanisms of motion

Abstract: Recent studies suggest that protein motions observed in molecular simulations are related to biochemical activities, although the computed time scales do not necessarily match those of the experimentally observed processes. The molecular origin of this conflicting observation is explored here for a test protein, cyanovirin-N (CV-N), through a series of molecular dynamics simulations that span a time range of three orders of magnitude up to 0.4 microseconds. Strikingly, increasing the simulation time leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Notably, many substates were not adequately sampled even in BPTI simulations, and the transitions leading to, or away from, them would not obey detailed balance principle, and would not lend themselves to quantitative evaluation of transition rates. These limitations of MD simulations, despite the capability of Anton technology to access processes 1-2 orders of magnitude longer than those investigated by conventional software, further highlight the significance of adopting low resolution models and methods for guiding or complementing full atomic simulations, using for example the ANM, [55][56][57][58] in order to sample functional events and/or extract robust features relevant to biological function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, many substates were not adequately sampled even in BPTI simulations, and the transitions leading to, or away from, them would not obey detailed balance principle, and would not lend themselves to quantitative evaluation of transition rates. These limitations of MD simulations, despite the capability of Anton technology to access processes 1-2 orders of magnitude longer than those investigated by conventional software, further highlight the significance of adopting low resolution models and methods for guiding or complementing full atomic simulations, using for example the ANM, [55][56][57][58] in order to sample functional events and/or extract robust features relevant to biological function.…”
Section: Discussionmentioning
confidence: 99%
“…These observations support the view that MD simulations usually hide information on potential reconfigurations that would take place at longer-time or larger-length scales. 56 Multiple runs and rigorous analyses by PCA-based tools appear to be essential for extracting cooperative/global movements robustly favored by the native contact topology.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, however, Liu et al suggested that simulations spanning a range of two orders of magnitude produce similar dominant motions. 41 This is an interesting result that cannot be overlooked; however, they consider only the most dominant motion, as opposed to comparing the whole fluctuation space, which was done in the current study. We previously showed that fitting to short simulations leads to systematic errors which manifest in the eigenvalue spectra.…”
Section: Introductionmentioning
confidence: 91%
“…The quantity 2D α is the variance of the distribution of the random angular jumps Δγ n ðtÞ of the random walker, and the exponent α is related to the speed of the diffusion (6). An exponent α < 1 corresponds to a subdiffusive regime (12)(13)(14)(15) previously observed in fluorescence experiments (16) and in MD simulations (5,6,(17)(18)(19) of proteins. The subdiffusion means that the random walker has a memory of its past (13).…”
mentioning
confidence: 99%